Finite element analysis of spiral strands with different shapes subjected to axial loads. (May 2015) - Stanova, Eva; Fedorko, Gabriel; Kmet, Stanislav; Molnar, Vieroslav; Fabian, Michal
Highlights: A new mathematical geometric model of spiral oval wire strands is proposed. Concrete forms of derived parametric geometric equations are presented. Results of FE analyses of four spiral strands with different shapes are presented. Responses of round, triangular and oval strands under axial loads are compared. Result ant stress and/or deformation behaviours are discussed. Abstract: In this paper a new mathematical geometric model of spiral one or two-layered oval wire strands are proposed and an accurate computational two-layered oval strand 3D solid model, which is used for a finite element analysis, is presented. The three dimensional curve geometry of wires axes in the individual layers of the oval strand consists of straight linear and helical segments. The present geometric model fully considers the spatial configuration of individual wires in the right and left hand lay strand. Derived geometric equations were used for the generation of accurate 3D geometric and computational models for different types of strands. This study develops 3D finite element models of two-layer spiral round, triangular and oval strands subjected to axial loads using ABAQUS/Explicit software. Accurate modelling and understanding of their mechanical behaviour is complicated due to the complex contact interactions and conditions that exist between individual spirally wound wires. Comparisons of predicted responses for the strands with different shapes and constructions are presented. Resultant stress and/or deformation behaviours are discussed.